2022
DOI: 10.1080/19490976.2022.2157200
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to prolonged amoxicillin treatment: long-term resilience of the microbiome versus long-lasting perturbations in the gut resistome

Abstract: The collateral impact of antibiotics on the microbiome has attained increasing attention. However, the ecological consequences of long-term antibiotic exposure on the gut microbiome, including antibiotic resistance, are still limited. Here, we investigated long-term exposure effects to amoxicillin on the human gut microbiome and resistome. Fecal samples were collected from 20 patients receiving 3-months of amoxicillin or placebo treatment as part of a Norwegian multicenter clinical trial on chronic low back pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…However, most available studies using metagenomics have focused on the gut resistome. In these studies, the reported outcomes on the resistome vary from no signi cant effects to increased antibiotic resistance gene load and diversity following antibiotic therapy (20,(70)(71)(72). For the oral microbiome, our knowledge is mostly restricted to a few studies indicating that the oral microbiome is more resilient to changes than the gut microbiome (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, most available studies using metagenomics have focused on the gut resistome. In these studies, the reported outcomes on the resistome vary from no signi cant effects to increased antibiotic resistance gene load and diversity following antibiotic therapy (20,(70)(71)(72). For the oral microbiome, our knowledge is mostly restricted to a few studies indicating that the oral microbiome is more resilient to changes than the gut microbiome (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The baseline host gut microbiota is influenced by a variety of factors including geographic location, diet, gender, age, drug therapy, host immunity, and disease. 84,[113][114][115][116][117][118][119] The abundance of Bifidobacterium spp. and Blautia spp.…”
Section: Baseline Gut Microbiotamentioning
confidence: 99%
“…130,131 Dhariwal et al found that amoxicillin treatment significantly reduced the proportion of health-related short-chain fatty acid-producing microbes in the host gut. 84 Cruz-Lebron et al found that chronic opioid use, which is widespread in the United States, caused severe intestinal dysfunction, with serious disruptions to host gut microbiota, intestinal bacterial metabolic profiles, and gut barrier integrity. 87 Hayase et al found that disruption of the baseline microbiota directly affected the antitumor efficacy of immune checkpoint inhibitors (ICIs).…”
Section: Baseline Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota is not only a sophisticated ecosystem, but also an important reservoir of antibiotics resistance genes (ARGs) ( Hu et al, 2013 ; Hofer, 2022 ). Several metagenomic analyses have revealed that the structure of the gut microbiota is markedly influenced by these resistance genes ( Dhariwal et al, 2023 ), with a shared network of ARGs existing between pathogenic and commensal gut microorganisms ( Forster et al, 2022 ). In order to solve the increasingly severe problem of drug resistance, we must understand how bacteria acquire and disseminate resistance genes in clinical settings.…”
Section: Introductionmentioning
confidence: 99%